Learn to navigate through deep neural networks - Wu, Keyu (Nanyang Technological University, 2020)
Autonomous navigation is a crucial prerequisite for mobile robots to perform various tasks while it remains a great challenge due to its inherent complexity. This thesis deals with the autonomous navigation problem using deep neural networks. It presents four main parts, i.e., an imitation learning based path planning algorithm, an imitation learning based online path planning method, a deep reinforcement learning based autonomous steering method, and a deep reinforcement learning based autonomous navigation method.